Conservation et restauration de la forêt tropicale du Panama : enjeux et pistes de solutions - Simon Bilodeau Gauthier; Pascal Côté (VertigO, 2005)
Although Panama is better known for its famous transoceanic canal, it is also the cradle of extraordinary biodiversity. However, as is the case in a growing number of tropical countries, it has also been subjected to extensive deforestation since the mid-1950s. Counteracting this trend will not likely be an easy task. For one, a growing population is increasing the adoption of shifting cultivation practices, a major cause of Panamanian forest destruction. Small landholders, while mainly responsible for this situation, are certainly not acting with bad intent. In considering that 60% of the rural population is living in poverty, it is clear that motivations for such actions relate to survival rather than profit. Nonetheless, not all is lost: 25% of the territory is protected, and several reforestation (plantation) and agroforestry projects have been undertaken in the last decades in order to offer a sustainable alternative to farmers. Despite the enormous potential of these alternatives, many obstacles still challenge and limit their widespread use. The starting costs are often beyond the farmers' financial means, and the local populations' needs are rarely consulted beforehand. Since solutions to the deforestation issue already exist, we have focused our attention on evaluating the different ways of increasing the success of the aforementioned alternative projects.